Aumolertinib-based comprehensive treatment for an uncommon site of EGFR exon 20 insertion mutations with multiple metastases non-small cell lung cancer: a case report. Issue 4 (21st February 2022) - Deng, Youjun; Yang, Chenglin; Liu, Wenyi; Cai, Songhua; Guo, Xiaotong
Abstract : EGFR exon 20 insertion mutation is a rare mutation subtype of EGFR mutations, with no approved treatment in China so far. The clinical treatments of advanced EGFR exon 20 insertion mutations in non-small cell lung cancer (NSCLC) are mainly based on EGFR-TKI, chemotherapy, ICI, and other therapies. However, the efficacy is not satisfactory. Aumolertinib is the third-generation EGFR-TKI independently developed in China, which has shown excellent efficacy and safety in phase 2 and 3 clinical trials. This study aimed to share a case of applying aumolertinib as the core combined with other treatments for a patient with multiple metastases in NSCLC with an uncommon site of EGFR exon 20 insertion mutations. The comprehensive treatment benefited the patient in terms of 10 months of progression-free survival and a significant improvement in quality of life. We discussed whether we could further explore the potential of aumolertinib in treating EGFR exon 20 insertion mutations through this case report.